Materiales didácticos multimedia para fortalecer el aprendizaje de la física en los estudiantes del segundo año de bgu de la unidad educativa fiscomisional Calasanz de la ciudad de Loja, año 2019 - Pasaca Guarnizo, Jefferson Alexander (2020)
This research entitled: multimedia teaching materials to strengthen the learning of physics in the students of the second year of the UGB of the Calasanz Fiscomisional Educational Unit of the city of Loja, year 2019, aims to determine whether multimedia teaching materials are effective tools to strengthen the learning of physics. It is developed under the following general objective: to investigate what is the relationship between the use of multimedia teaching materials and the strengthening of physics learning in the students of the second year of the UGB of the Calasanz Fiscomisional Educational Unit, of the city of Loja. In addition, it has as specific objectives: to use multimedia teaching materials and evaluate the learning of physics in the students of the second year of the UGB, before and after the use of such materials. To comply with the objectives and verify the hypothesis, the learning of physics in students is evaluated through various tests, before and after the use of multimedia teaching materials designed by the researcher. The results obtained show that the learning level of the students in the pretest is 6,11/10 and in the posttest is 8,03/10; then, using the Student's T-test for related samples, it is determined that the difference between the means obtained in the pre and posttest is significant. Therefore, it is concluded that there is a positive relationship between the analyzed variables and that the use of multimedia teaching materials allows to strengthen the learning of physics in the students of the second year of the UGB.